Vegetational history of Nachiketa Tal, Garhwal Himalaya, India - Sharma, Chhaya; Gupta, Asha (Journal of Nepal Geological Society, 1995)
Vegetational history traced back to 1500 years (based on 14C dating) and the deduced corresponding climate for the temperate region of Uttarkashi in Garhwal Himalaya is discussed in the paper. Pollen analysis of 2 metres deep sedimentary profile dug out from Nachiketa Tai, has revealed the existence of thick broad-leaved forests in the region, evidenced by the dominance of arboreal pollen over non-arboreals, Quercus dominated in these forests, associated with Alnus, Betula, Carpinus, Juglans, Rhododendron, Ulmus, Celtis, Aesculus, Corylus, etc.The non-arboreal ground vegetation comprised mainly thegrasses alongwith few other scattered taxa. Moderate distribution of ferns and peponderance of aquatics, reflect to the prevailing wet habitat conditions inside the forest. Overall vegetational scenario thus depicts warm-temperate and humid climate during the period and probably even earlier which has continued till today without much change except for some minor fluctuations. A gradual decline in oak witnessed around 200 years ago and simultaneous increase in non-arboreal elements as well as culture pollen is indicative of the advent of agricultural practices in the region.